Defective Porous Carbon Polyhedra Decorated with Copper Nanoparticles for Enhanced NIR‐Driven Photothermal Cancer Therapy. Issue 1 (1st December 2019) - Weng, Yangziwan; Guan, Shanyue; Wang, Li; Lu, Heng; Meng, Xiangmin; Waterhouse, Geoffrey I. N.; Zhou, Shuyun
Abstract: Currently, there is tremendous interest in the discovery of new and improved photothermal agents for near‐infrared (NIR)‐driven cancer therapy. Herein, a series of novel photothermal agents, comprising copper nanoparticles supported on defective porous carbon polyhedra are successfully prepared by heating a Cu‐BTC metal–organic framework (MOF) precursor at different temperatures ( t ) in the range 400–900 °C under an argon atmosphere. The copper nanoparticle size and carbon defect concentration in the obtained products (denoted herein as Cu@CPP‐ t ) increase with synthesis temperature, thus imparting the Cu@CPP‐ t samples with distinct NIR absorption properties and photothermal heating responses. The Cu@CPP‐800 sample shows a remarkable photothermal conversion efficiency of 48.5% under 808 nm laser irradiation, representing one of the highest photothermal efficiencies yet reported for a carbon‐based photothermal agent. In vivo experiments conducted with tumor bearing nude Balb/c mice confirm the efficacy of Cu@CPP‐800 as a very promising NIR‐driven phototherapy agent for cancer treatment. Results encourage the wider use of MOFs as low cost precursors for the synthesis of carbon‐supported metal nanoparticle composites for photothermal therapy. Abstract : The copper nanoparticles supported on defective porous carbon polyhedra are successfully prepared by heating a Cu‐BTC metal organic framework (MOF) precursor at different temperatures under an argon atmosphere. The copper nanoparticle size and carbon defect concentration in the obtained products increase with synthesis temperature, thus imparting the samples with distinct NIR absorption properties and photothermal heating reponses.